The Magic in 2-Channel Sound Reproduction - Why is it so Rarely Heard? - Siegfried Linkwitz, (International Journal of Architectural Engineering Technology, 2015)
Hearing, finding the direction, distance and significance of a source of sound in various acoustic environments, is a survival mechanism in the evolution of living organisms. Hearing two strongly correlated sources of sound, either from earphones or two loudspeakers, is an unnatural phenomenon, from which the ear-brain apparatus is asked to draw an illusion of reality. Misleading cues must be eliminated from the sound presentation for the illusion to happen convincingly. In the case of earphone presentation, which typically suffers from a high degree of distance distortion, i.e. distance foreshortening, the ear signals must change with head movement to externalize the illusion. In the case of loudspeaker presentation there is already the distance between listener and speakers, which typically is perceived as the minimum distance to the illusionary aural scene or phantom scene. But that scene is usually hard bounded by the speakers, which are recognized as such by the ear-brain perceptual apparatus. One or the other speaker is preferred as the source, when the listener moves a short distance away laterally from the "sweet spot". In a reverberant room, where the listener not only hears the direct sound but also the reflected sound, i.e. the off-axis radiated sound, the ear-brain perceptual apparatus must be allowed to withdraw attention from room and speakers and focus attention upon the direct sound to create a convincing illusion of the reproduced acoustic event. For this to happen misleading perceptual cues must be eliminated. The speakers must be placed so that reflections are delayed relative to the direct sound. The speakers must be free from spurious resonant radiation and their off-axis radiation must follow their on-axis frequency response for the reverberant sound to be neutral. The polar radiation pattern must be essentially either omni-directional, cardioid or dipolar, aiming for constant directivity. The speakers must be acoustically small, yet capable of realistic volume levels at low non-linear distortion. Two prototype speakers and the evolution of their radiation pattern design will be discussed: a full-range, acoustically small dipole and a hybrid, omni-cardioid-dipole design. Either speaker is capable of disappearing from perception and rendering an aural scene in a reverberant room that is like a magic act.